Performance of exporting shrimps and dry fishes from Bangladesh - Sen, BR; Islam, T; Alam, K; Hassan, F (Journal of the Bangladesh Agricultural University, 2016)
This study shows the present status of exporting shrimps and dry fishes from Bangladesh in the pre-and -post liberalization period, estimates the growth rate and instability of exporting shrimps and dry fishes for earnings, quantity & price for five years. Recent status presents that farming of shrimp and processing of dry fish are increasing over the year. Status of exporting shrimp & dry fish (value, volume & price) are decreasing in recent years compared to previous years. The overall estimated growth of exported shrimp and dry fish (value) were found 19.48% and 16.53% and (volume) were found 11.52% and 12.86%, respectively. On the other hand, overall estimated export growth of shrimp & dry fish (price) were 175.94% and 37.58%, respectively. Instability in shrimp export earnings was found the highest in period I which was 62.16% and the lowest in period II which was 12.56%. Dry fish export instability was the highest for period I which was 128.08% & the lowest percentage was 54.49% in period II. Instability in quantity export of shrimp was found the highest in period I at 63.29% whereas it was 155.92% in period I for dry fish export and the lowest percentage for both were 14.5% & 48.66% in period II, respectively. On the other hand, instability in prices of exported shrimp & dry fish were found the highest in period I which were 25.26% & 140.63%, respectively. The lowest percentage for shrimp in period II which was 11.29% and for dry fish it was 63.56% in period III. It also affects export of shrimp & dry fish from Bangladesh. The circumstances of shrimp & dry fish export demand different institutional supports to enhance the marketing activities and to strengthen the competitive position in the international market with a view to ensuring more contribution to our economy. J. Bangladesh Agril. Univ. 14(1): 69-74, June 2016